Going off antiretroviral treatment in a closely monitored HIV “cure” trial: longitudinal assessments of acutely diagnosed trial participants and decliners - Henderson, Gail E (J Int AIDS Soc, 2019)
INTRODUCTION: The South East Asia Research Collaboration in HIV (SEARCH) RV411 clinical trial in Thailand was a systematic investigation of analytic treatment interruption (ATI) in individuals diagnosed and treated since Fiebig stage I acute HIV infection. Here, we explore decision‐making processes and perceptions of trial participation in a phase I trial that raised important ethical considerations, to identify potential areas of improvement in this relatively new field of HIV research. Similar considerations apply to other HIV phase I trials, especially those involving ATI, making this trial a model to identify challenges and opportunities in promoting informed choice. METHODS: Using longitudinal semi‐structured interviews and a validated questionnaire, we examined how decisions to join or decline the trial were made, whether there was evidence of decisional conflict, and reactions to the trial outcomes. We also explored contrasting views and experiences in this small trial cohort. We report analyses of data from these questionnaires and interviews, conducted from February through December of 2016 with the 14 SEARCH cohort participants who either joined (n = 8) or declined (n = 6) participation in RV411. RESULTS: The eight participants and six decliners had low overall decisional conflict, which remained low over time. Decision making was more difficult for decliners than participants, at least initially. While all interviewees described being satisfied with their decisions, our study identified important negative consequences for a few individuals, including seroconversion, negative experiences with optional procedures and disappointment due to rapid viral rebound. CONCLUSIONS: Although our results reflect the experiences of a small group invited to join this trial, our overall finding of low decisional conflict even while some individuals reported negative experiences provides lessons for clinical trial investigators. We developed points‐to‐consider in helping participants make informed choices, to support participants during the trial and to support decliners in their decisions.